1992
DOI: 10.1177/000841749205900106
|View full text |Cite
|
Sign up to set email alerts
|

The Manpower Shortage in Occupational Therapy: Implications for Ontario

Abstract: A consistently increasing imbalance between the supply of and demand for occupational therapists has led to a critical manpower shortage in occupational therapy. Based on a review of various government reports and related literature, this paper provides an overview of the extent of this manpower problem, identifies factors affecting retention and attrition of occupational therapists and discusses strategies to improve retention and reduce attrition. To address the supply-demand imbalance, recommendations in re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0
1

Year Published

2001
2001
2018
2018

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 33 publications
0
13
0
1
Order By: Relevance
“…17,18 An individual with higher job satisfaction is less likely to depart from a profession than an individual with lower job satisfaction. 18 Factors affecting job satisfaction exist in every profession and have been studied extensively in other health professions, including medicine, 19 occupational therapy, 20,21 and physical therapy. 22,23 In 1985, Spector 24 developed the Job Satisfaction Survey (JSS) to measure 9 subscales of satisfaction: supervision, pay, contingent rewards (appreciation and recognition), fringe benefits, promotional opportunities, coworkers, nature of work, work conditions, and communication.…”
Section: Job Satisfactionmentioning
confidence: 99%
“…17,18 An individual with higher job satisfaction is less likely to depart from a profession than an individual with lower job satisfaction. 18 Factors affecting job satisfaction exist in every profession and have been studied extensively in other health professions, including medicine, 19 occupational therapy, 20,21 and physical therapy. 22,23 In 1985, Spector 24 developed the Job Satisfaction Survey (JSS) to measure 9 subscales of satisfaction: supervision, pay, contingent rewards (appreciation and recognition), fringe benefits, promotional opportunities, coworkers, nature of work, work conditions, and communication.…”
Section: Job Satisfactionmentioning
confidence: 99%
“…It has been well reported that the supply of trained therapists in Australia, Canada and the United States is lagging behind the present and anticipated future demand and that this has led to critical manpower shortages in occupational therapy (Graham and Allen, 1990;Salvatori et al, 1992;Trickey and Kennedy, 1995). Price (1993) suggested that occupational therapists and occupational therapy students hold a negative image of the psychiatric field.…”
Section: Staff Recruitment and Retentionmentioning
confidence: 99%
“…In the Australian study conducted by Cusick et al (1993) a negative perception of the mental health work setting and role was found to be influenced by social stigma, disillusionment with the role of occupational therapy, inadequate course preparation and difficulty dealing with chronicity. In Ontario, Canada, continually escalating client care requirements within an environment of limited numbers of occupational therapy graduates and lack of seniority or upward mobility were some of the main reasons for manpower shortages in occupational therapy (Salvatori et al, 1992). Staff shortages are a concern because they put pressure on staff to fulfil the demands of the job.…”
Section: Staff Recruitment and Retentionmentioning
confidence: 99%
“…Job satisfaction within the health professions has been a focus since an author 131 examined the job satisfaction of nurses in the 1940s. Since then, job satisfaction has been studied in various health care professionals, including physicians, 132 occupational therapists, 133,134 and physical therapists. [134][135][136] Initial research on job satisfaction in athletic training began in the 1980s with a look at burnout syndrome.…”
Section: Consequences Of Work-life Conflictmentioning
confidence: 99%
“…Since then, job satisfaction has been studied in various health care professionals, including physicians, 132 occupational therapists, 133,134 and physical therapists. [134][135][136] Initial research on job satisfaction in athletic training began in the 1980s with a look at burnout syndrome. 4 Certain factors greatly influence job satisfaction within athletic training: for example, pay, 137 work-family conflict, 138 and organizational constraints.…”
Section: Consequences Of Work-life Conflictmentioning
confidence: 99%